KELAS BAHASA INGGRIS UNTUK UMKM DALAM MENDUKUNG PEMASARAN PRODUK LOKAL KE PASAR GLOBAL - Ruri Supatmi; Rangga Mega Putra; Ariyani Ariyani (MAJU : Indonesian Journal of Community Empowerment, 2026)
This Community Service Program was conducted in Adirejo Village, Pekalongan, East Lampung, with the aim of enhancing practical English skills among MSME actors to support the marketing of local products in global markets. The program was designed as a practical English class tailored to business needs, focusing on product description writing, basic business communication, and digital marketing strategies. The implementation applied a task-based learning approach through stages of preparation, counseling, training, mentoring, and demonstration. The results showed significant improvements: 80% of participants successfully wrote product descriptions in English with appropriate grammar and marketing vocabulary, 70% actively used English in simulated business conversations, and 60% produced promotional content in English for social media and marketplaces. Furthermore, participants’ confidence increased by 22% based on pre- and post-program questionnaires. These findings confirm that practice-oriented training effectively strengthens MSMEs’ capacity to interact with international buyers and expand their market reach. In conclusion, this PKM program successfully provided applicable English skills relevant to MSMEs’ needs, while also developing a replicable learning model that can be implemented in other regions as a sustainable community empowerment strategy.